2023
DOI: 10.1002/jsp2.1276
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based detection and classification of lumbar disc herniation on magnetic resonance images

Weicong Zhang,
Ziyang Chen,
Zhihai Su
et al.

Abstract: BackgroundThe severity assessment of lumbar disc herniation (LDH) on MR images is crucial for selecting suitable surgical candidates. However, the interpretation of MR images is time‐consuming and requires repetitive work. This study aims to develop and evaluate a deep learning‐based diagnostic model for automated LDH detection and classification on lumbar axial T2‐weighted MR images.MethodsA total of 1115 patients were analyzed in this retrospective study; both a development dataset (1015 patients, 15 249 ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…With more improvements in AI technology, the future could be automated reporting of radiological investigations, saving time and providing optimal results comparable with human reporting. Existing studies on the diagnosis of lumbar disk degeneration are shown in Table 1 [ 41 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…With more improvements in AI technology, the future could be automated reporting of radiological investigations, saving time and providing optimal results comparable with human reporting. Existing studies on the diagnosis of lumbar disk degeneration are shown in Table 1 [ 41 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study of lumbar disc herniation typing method based on deep learning, Gao et al [3] proposed a push-pull regularization network (PPR) module and improved classification accuracy by integrating it with image classification networks, the results showed that after adding the PPR module, networks such as GoogleNet, ResNet, and VGG improved accuracy in the Pfirmmann degeneration five classification task of lumbar intervertebral discs, with an average improvement of 8%; Zhang et al [4] used the Faster R-CNN algorithm to detect the lumbar disc region in magnetic resonance axial image. images, and then used the ResNet101 algorithm for lumbar disc herniation typing, and the accuracy of the proposed automatic diagnostic method five classification can reach 87.7%; Tsai et al [5] used the improved YOLOv3 algorithm to detect lumbar disc herniation regions in magnetic resonance sagittal images, and their proposed method is able to still obtain high accuracy.…”
Section: Introductionmentioning
confidence: 99%